Recent changes in London’s money market arrangements - J.S.G. WILSON (PSL Quarterly Review, 2013)
Despite numerous changes over the past 20 years, there can be little doubt that the 12 discount houses still constitute the core of money market arrangements in London. They form the London Discount Market Association and they have accounts with the Bank of England, which give them access to the Bank of England as lender of last resort to the banking system. The Bank of England is now attempting to ensure that the discount houses maintain prudent business practices at all times and do not expose themselves excessively to risks that they may not be able to meet if the value of investments falls.The author provides an in-depth review of the recent changes to London’s money market arrangements concluding that on the whole, the new rules are a formalisation of good working practices.